2021
DOI: 10.4102/sajce.v11i1.1023
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ perspectives on learners with reading and writing difficulties in mainstream government primary schools in Mauritius

Abstract: Background: Although Mauritius has adopted an inclusive education policy for learners with special education needs, it has not yet been implemented. Little is known about how teachers support learners experiencing reading and writing difficulties (RWD) in mainstream government primary schools.Aim: The aim of the study was to describe the perspectives of mainstream primary school teachers in Mauritius about learners with RWD and inclusive education.Setting: The data collection took place at the respective schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The study on perspectives of teachers on learners with RWD in Mauritius further showed that teachers were able to identify learners with such problems in their classes but were unaware of symptoms and causes of RWD (Veerabudren et al 2021a(Veerabudren et al , 2021b. Teachers do not receive any training in inclusive education or how to assist learners with RWD in a regular classroom (Veerabudren et al 2021a(Veerabudren et al , 2021b. A study about the perspectives of parents with children with RWD in the same setting also showed that parents have limited information about the symptoms and causes of their child's RWD, therefore describing children with RWD mostly as lazy or ascribing RWD to poor teaching methods.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study on perspectives of teachers on learners with RWD in Mauritius further showed that teachers were able to identify learners with such problems in their classes but were unaware of symptoms and causes of RWD (Veerabudren et al 2021a(Veerabudren et al , 2021b. Teachers do not receive any training in inclusive education or how to assist learners with RWD in a regular classroom (Veerabudren et al 2021a(Veerabudren et al , 2021b. A study about the perspectives of parents with children with RWD in the same setting also showed that parents have limited information about the symptoms and causes of their child's RWD, therefore describing children with RWD mostly as lazy or ascribing RWD to poor teaching methods.…”
Section: Introductionmentioning
confidence: 99%
“…A study on teacher perspectives of learners with RWD in mainstream government schools in Mauritius revealed that the number of learners in classes ranged between 15 and more than 35, which indicates variation across countries (Veerabudren et al 2021a(Veerabudren et al , 2021b. Many teachers were not adequately trained to support learners with RWD in an inclusive education setting (Veerabudren et al 2021a(Veerabudren et al , 2021b. A low remuneration scale may also decrease teachers' job satisfaction (Gamero Burón & Lassibille 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On this background, it is noted with great concern that factors that influence teachers in selecting inclusive teaching strategies in the rural foundation phase have not been researched in Limpopo, South Africa. According to Veerabudren, Kritzinger and Ramasawmy (2021) in an inclusive classroom, the role of teachers is to consistently and creatively modify their teaching strategies in order to include all learners learning needs. Even though there is no single definition of what inclusive pedagogy is, Floria (2015) defines it as an approach to teaching and learning that supports teachers to respond to individual differences amongst learners but avoids the marginalisation that occurs because some students are treated differently.…”
Section: Introductionmentioning
confidence: 99%